The Challenges of Gender Diversity in Boards of Directors: An Australian Study with Global Implications - Suzanne Young; Karen Farquharson; Daswin De Silva; Paul Mather (Global Challenges)
Abstract Despite gender diversity being driven by institutional bodies, companies have been relatively slow to diversify. In this study, it is investigated that how Australian boards select new directors, and how those selection processes affect their recruitment of women. In‐depth interviews are conducted of those with first‐hand experience of board appointments, followed by the thematic analysis and the application of natural language processing techniques to identify emotions and sentiment associated with these themes. The findings indicate that boards are adopting a social rather than rational approach to board selection. They are using networks, recruitment agencies, skills matrices and pools which on the surface appear to broaden the diversity of board members. But if they are not actively seeking gender diversity these methods can still limit diversity. For women, the lack of progress and barriers of access are resulting in high intensity of negative emotions. A key contribution of the research is the intersection of social approaches to board appointment and social identity theory with the dynamics of gender. Boards need to prioritize diversity for it to be achieved. There is a need for more active methods of recruitment and expansion of the networks and pools where directors are traditionally sought. Institutions can drive change through increasing targets and requiring enhanced reporting.